Analisa Pengaruh Waktu Penahanan (Holding Time) Pada Proses Tempering Terhadap Sifat Mekanis Baja Karbon Menengah Hasil Pengelasan Fcaw (Flux Core Arc Welding) - Rey Joy Toding Padang; Nevada. J.M Nanulaita; Cley Talkua; Agustinus O. Lopuhaa; Faizatur Rohmah (Journal Mechanical Engineering, 2023)
FCAW (Flux Core Arc Welding) welding is a type of welding process or joining metal materials that uses a heat source from electrical energy which is converted or converted into heat energy. a roll and uses gas as a protector for the weld metal which melts during the welding process. The content of medium carbon steel is 0.3%C - 0.6%C. This carbon steel has advantages compared to low carbon steel, medium carbon steel has stronger mechanical properties with a higher level of hardness than low carbon steel. . Before and after welding carbon steel materials, material testing will be carried out. With this test, it is hoped that the hardness and bending strength of the material will be known. The method used is a quantitative method including experimental research. With a plate thickness of 5mm, a variation of the V seam angle with an angle of 45° with a depth of 2.5mm. Using a stickout height of 5mm by varying the holding time, namely 30 minutes, 60 minutes, 90 minutes for FCAW welding  Keywords: Carbon steel, FCAW (Flux Core Arc Welding), Holding Time, Hardness Test, Bending Test